Prevalence of Chronic Kidney Disease in Patients Undergoing Cardiac Rhythm Device Removal. Issue 1 (11th July 2012) - Asif, Arif; Carrillo, Roger; Garisto, Juan Domingo; Monrroy, Mauricio; Khan, Rao Ali Hashim; Castro, Hector; Merrill, Donna; Ali, Ayesha S.; Pai, Amy Barton; Waldman, Jonathan; Salman, Loay
Abstract Cardiac implantable electronic device (CIED) leads can cause central venous stenosis (CVS). In addition, these devices can get infected. Both are critically important considerations in patients with chronic kidney disease (CKD) for at least two reasons: (i) central veins serve as the final pathway should these patients need an arteriovenous access to provide dialysis therapy; and (ii) the presence of renal failure increases the risk of CIED infection. In this analysis, we investigated the prevalence as well as the degree of chronic kidney disease in patients harboring a CIED. Patients undergoing CIED removal were evaluated from 2001 to 2011. The patients were categorized into CKD stage I–V based on National Kidney Foundation‐Dialysis Outcomes Quality Initiative guidelines. A total of 503 patients underwent CIED removal. Demographic characteristics revealed that 30% had hypertension, 44% were diabetics, 77% had coronary artery disease, and 84% suffered from congestive heart failure. Ninety percent (452/503) of the patients had CKD (stage I = I9 [4.2%], stage II = 189 [41.8%], stage III A = 96 [21.2%], stage III B = 59 [13.0%], stage IV = 45 [9.9%], and stage V = 44 [9.7%]). Overall, 148 (32.7%) patients (stage III B, stage IV, and stage V) of 452 had advanced renal failure. The results of this study reveal that one‐third of CIED patients undergoing device removal have advanced chronic kidney disease.